Buffer stock savings in a New-Keynesian business cycle model - Katrin Rabitsch; Christian Schoder (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
We introduce the tractable buffer stock savings setup of Carroll and Toche (2009 NBER Working Paper) into an otherwise conventional New-Keynesian dynamic stochastic general equilibrium model with financial frictions. The introduction of a precautionary saving motive arising from an uninsurable risk of permanent income loss, affects the model's properties in a number of interesting ways: it produces a more hump-shaped reaction of consumption in response to both supply (technology) and demand (monetary) shocks, and more pronounced reactions in response to demand shocks. Adoption of the buffer stock savings setup thus offers a more microfounded way, compared to, e.g., habit preferences in consumption, to introduce Keynesian features into the model, serving as a device to curbing excessive consumption smoothing, and to attributing a higher role to demand driven fluctuations. We also discuss steady state effects, determinacy properties as well as other practical issues.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: 330